Sudahkah Akuntansi Kita Berpihak Pada Rakyat? (Refleksi Pemikiran Mohammad Hatta)(Has Our Accounting Served the People? A Reflection of Mohammad Hatta’s Thought) - Ramandha, Balance Stefany; Septyan, Krisno (Akutansi Bisnis & Manajemen ( ABM ), 2025)
This study aims to align accounting practices in Indonesia with the principles of a people-centered economy. Drawing on the philosophical ideas of Mohammad Hatta, a synchronic ontological approach is employed to foster a theoretical dialogue between contemporary thinkers and Hatta. The findings reveal that people-centered accounting prioritizes promoting domestic products and fosters nationalism by integrating local cultural values into accounting standards. This model is expected to transform accounting practices to reflect local wisdom better and contribute to societal well-being. The study offers a new perspective on how cultural values and ideologies can shape accounting practices, thus contributing to the development of culture-based accounting aligned with national development and economic sovereignty.